2016
DOI: 10.1053/j.gastro.2015.10.042
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Characterization of Diminutive Colorectal Polyp Histology Using Narrow-Band Imaging: Implications for the Resect and Discard Strategy

Abstract: BACKGROUND & AIMS Narrow-band imaging (NBI) allows real-time histologic classification of colorectal polyps. We investigated whether endoscopists without prior training in NBI can achieve the following thresholds recommended by the American Society for Gastrointestinal Endoscopy: for diminutive colorectal polyps characterized with high confidence, a ≥90% negative predictive value for adenomas in the rectosigmoid and a ≥90% agreement in surveillance intervals. METHODS Twenty-six endoscopists from 2 tertiary c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
87
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(89 citation statements)
references
References 36 publications
2
87
0
Order By: Relevance
“…In several studies, NBI was demonstrated to allow a reliable optical diagnosis of colonic lesions when used by appropriately trained endoscopists, and to improve diagnostic accuracy in lesion assessment [73, 75-77]. At present, there is a paradigm shift in the management of diminutive colorectal polyps (≤5 mm), advocating the use of optical biopsy with endoscopic technologies rather than histopathology for polyp characterization and subsequent assignment of surveillance intervals, without affecting its efficacy in reducing the future risk of colorectal cancer [78, 79].…”
Section: Colonmentioning
confidence: 99%
“…In several studies, NBI was demonstrated to allow a reliable optical diagnosis of colonic lesions when used by appropriately trained endoscopists, and to improve diagnostic accuracy in lesion assessment [73, 75-77]. At present, there is a paradigm shift in the management of diminutive colorectal polyps (≤5 mm), advocating the use of optical biopsy with endoscopic technologies rather than histopathology for polyp characterization and subsequent assignment of surveillance intervals, without affecting its efficacy in reducing the future risk of colorectal cancer [78, 79].…”
Section: Colonmentioning
confidence: 99%
“…Other studies have reported that academic and community endoscopist can meet the PIVI threshold of at least 90% NPV for adenomas in diminutive rectosigmoid lesions 5,[9][10][11][12][13][14] , including when SSPs were counted as adenomas [9][10][11]13 . We found that absolute prevalence of SSPs in diminutive rectosigmoid lesions that appear hyperplastic was 0.6% to 2.1% according to pathology interpretations by three expert pathologists.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Also anecdotally, we have observed interpretations of SSA/P in rectosigmoid serrated lesions. The precise prevalence of SSA/P in diminutive rectosigmoid M A N U S C R I P T , or did not specify findings in the rectosigmoid 13 or excluded SSPs 14 . None of the studies used additional expert assessment of pathology to determine how interobserver variability in SSP interpretation would affect the prevalence of SSP in distal diminutive polyps.…”
Section: Introductionmentioning
confidence: 99%
“…Endoscopic criteria 4 can also be used to reliably identify most precancerous colorectal lesions as belonging to the conventional adenoma versus serrated class 5 . Commonly used endoscopic criteria for differentiation of conventional adenomas from serrated class lesions use surface features such as the microvascular pattern and the shape of pits 4 .…”
Section: Introductionmentioning
confidence: 99%